Stress-Based Weibull Method to Select a Ball Bearing and Determine Its Actual Reliability - Piña Monarrez, Manuel Román (2020)
Since the designed bearing’s reliability of 90% was determined in a lab environment, it does not represent the actual used environment. In this paper, a new methodology to determine the actual reliability that corresponds to the use conditions is o ered. This new method is based on the standard method used to select the ball bearing. The proposed method is based on the two parameters of Weibull distribution, where the shape ( ) and scale ( ) parameters are both determined from the Hertz contact stresses values, which are generated under the surface of the motionless outer race, and by the forces transmitted between the ball and the outer race. Therefore, the derived reliability is di erent from the 90% index o ered by manufacturers.